Epigenetic regulation in tomato fruit ripening - Ming, Yucheng; Jiang, Libo; Ji, Dongchao (Frontiers in Plant Science, 2023)
Fruit ripening is a crucial stage in quality development, influenced by a diverse array of internal and external factors. Among these factors, epigenetic regulation holds significant importance and has garnered substantial research attention in recent years.Fruit ripening is the key stage of quality formation, which is affected by diversely internal and external factors. Among them, epigenetic regulation is an important factor and has been the focus of research in recent years. Here, this review aims to discusses the breakthrough in epigenetic regulation of tomato (Solanum lycopersicum) fruit ripening, including DNA/ methylation, N 6 -Methyladenosine mRNA modificationRNA methylation, histone demethylation/deacetylationmodification, and non-coding RNA.Through this brief review, we seek to enhance our understanding of the regulatory mechanisms governing tomato fruit ripening, while providing fresh insights for the precise modulation of these mechanisms.This brief review was compiled to enrich our understanding towards the regulatory mechanisms of fruit ripening and gives new insight for accurately regulating the mechanisms of fruit ripening.